Students’ Literacy Levels on the Use of Campus Libraries for Academic Needs - Nasywa Nuro Anjani; May Sha Aurellita Antono Putri; Maulana Al Akbar; Arsyilla Pasha Riyandana; Wafirotul Laila; Joko Tri Nugraha (Jurnal El-Pustaka, 2026)
The development of information technology has driven changes in student behavior in accessing and utilizing information sources, including campus libraries. Although access to information has become easier through the internet, utilizing credible academic sources remains a challenge. This study aims to analyze the level of information literacy of students in utilizing campus libraries to support learning needs. This study used a descriptive quantitative approach with a survey method of 428 respondents, students of the Faculty of Social and Political Sciences, Tidar University, class of 2024 and 2025. The research instrument was a questionnaire that measured five indicators of information literacy, namely the ability to identify information needs, search for information, evaluate information, use information, and utilize campus libraries. Data were analyzed using descriptive statistical techniques with percentage score calculations. The results showed that the level of information literacy of students was in the high category for all indicators. The ability to evaluate information obtained the highest score of 82.94%, followed by the ability to use information at 78.79%, the ability to identify information needs at 76.49%, utilization of campus libraries at 72.1%, and the ability to search for information at 71.78%. These findings indicate that students have good abilities in accessing, assessing, and utilizing information to support academic activities. However, there is still a tendency to use instant sources from the internet over more credible academic sources. The conclusion of this study confirms that students' information literacy is relatively good, but needs strengthening in the aspects of critical evaluation and optimizing the use of academic sources through campus libraries. This study recommends strengthening library-based information literacy programs to improve the quality of student learning.